Perifolliculitis capitis abscedens et suffodiens treatment with tumor necrosis factor inhibitors and baricitinib: A case report and literature review - Yu, Yuanting; Ding, Xiaojie; Guo, Fei; Ze, Kan; Sun, Xiaoying; Li, Xin (Frontiers in Medicine, 2023)
Abstract Rationale: Perifolliculitis capitis abscedens et suffodiens (PCAS), also known as dissecting cellulitis of the scalp (DCS), is a part of the “follicular occlusion tetrad” that also includes acne conglobate (AC), hidradenitis suppurativa (HS), and pilonidal sinus, which share the same pathogenic mechanism, such as follicular occlusions, follicular ruptures, and follicular infections. Patient Concerns: A 15-year-old boy had multiple rashes on the scalp accompanied by pain. Diagnosis: The patient was diagnosed with PCAS or DCS based on the clinical manifestations and laboratory examinations. Interventions: The patient was initially administered adalimumab 40 mg biweekly and oral isotretinoin 30 mg daily for 5 months. Because the initial results were insufficient, the interval between adalimumab injections was extended to 4 weeks, and isotretinoin was changed to baricitinib 4 mg daily for 2 months. When the condition became more stable, adalimumab 40 mg and baricitinib 4 mg were administered every 20 and 3 days, respectively, for 2 more months until now. Outcomes: After 9 months of treatment and follow-up, the original skin lesions of the patient were almost cured, and most inflammatory alopecia patches disappeared. Conclusions: Our literature review did not find any previous reports on treating PCAS with TNF-α inhibitors and baricitinib. Accordingly, we presented the first successful treatment of PCAS with this regimen. Overall, the proposed regimen can be efficient, effective, non-invasive, and safe for treating PCAS.